Caffeic acid modulates methane production and rumen fermentation in an opposite way with high‐forage or high‐concentrate substrate in vitro. (26th November 2020) - Jin, Qing; You, Wei; Tan, Xiuwen; Liu, Guifen; Zhang, Xianglun; Liu, Xiaomu; Wan, Fachun; Wei, Chen
Abstract: BACKGROUND: Plant secondary metabolites, including tannins, saponins and phenolic acids, possess potential methane (CH4 ) inhibition bioactivity. Caffeic acid (CA), as one of the typical phenolic acids, serves as a promising rumen CH4 inhibitor, but the underlying mechanisms and investigations with typical formulated rations are still not well documented. Therefore, a batch culture study was conducted to investigate the effects of CA on methanogenesis, rumen fermentation and growth of ruminal microorganisms when high‐forage or high‐concentrate substrates are fermented. RESULTS: After 48 h incubations, adding CA up to 40 g kg −1 dry matter linearly reduced ( P < 0.05) the disappearance of dry matter, neutral detergent fiber (NDFD), total gas, methanogenesis, total volatile fatty acid and 16S rDNA copy numbers of Ruminococcus albus and Butyrivibrio fibrisolvens, and increased 16S rDNA copy numbers of methanogens for the high‐forage treatment. For the high‐concentrate treatment, CA exerted opposite effects ( P < 0.05) on the above variables, except that CA did not affect ( P > 0.05)16S rDNA copy numbers of methanogens or R. albus . CONCLUSION: Caffeic acid inhibited in vitro methanogenesis and rumen fermentation with high‐forage substrate incubation. Contrarily, CA benefited in vitro fermentation and enhanced methanogenesis with high‐concentrate substrate incubation. It suggests that CA modulates methanogenesis and rumen fermentation mainly by affecting the growth of cellulolytic bacteria in vitro . © 2020 Society of Chemical Industry